ANALISIS MAQOSIDUS SYARIAH IMAM AS-SYATIBI DALAM MODEL FILANTROPI KOIN NU UNTUK PEMBERDAYAAN EKONOMI MASYARAKAT - Amin, M. Zaki; Rizal, Ahmad (Al-Maslahah : Jurnal Ilmu Syariah, 2025)
LAZISNU is paving the way for lower and middle class people who want to give alms through the NU Coin scheme. With the NU Coin program, they can still make donations without any objections because people can make small donations. The purpose of this research is to analyze the philanthropic model of people's economic empowerment in Koin NU through the description of Imam Syatibi's Maqāṣid Al-Sharīʿah. The research method used is a qualitative descriptive analysis approach. Sampling was conducted in several villages in Krezingan Subdistrict and at the LAZIZNU (Lembaga Amil Zakat and Sedekah NU) office in Krezingan Subdistrict. The management of NU Coins to improve community welfare is carried out by LAZIZNU Krejengan District, namely: collection of Infaq funds through NU Coins, data collection of Mustahik Infaq who are entitled to receive assistance, and finally the process of distributing Infaq in various forms. financial / economic assistance for the poor Empowerment provides financing. The management of NU coins at LAZIZNU Krejengan District is also in line with the concept of Maqashid Shari'ah because it contains an element of welfare in the form of economic empowerment.